Multiple Desmoplastic Cellular Neurothekeomas in Child: Report of the First Oral Case and Review of the Literature - Almeida, Tatiana Fernandes Araújo; Verli, Flaviana Dornela; dos Santos, Cássio Roberto Rocha; Falci, Saulo Gabriel Moreira; Almeida, Luciana Yamamoto; Almeida, Lana Kei Yamamoto [UNESP]; Mesquita, Ana Terezinha Marques; León, Jorge Esquiche (Springer Nature, 2018)
Cellular neurothekeomas (CNs) are distinctive benign tumors of uncertain histogenesis, with predilection for the skin of the head and neck region. We describe the first case of multiple desmoplastic CNs (DCNs) affecting the oral cavity in a 9-year-old girl. Histopathologic evaluation showed a proliferation of spindle and epithelioid cells, forming nests and bundles, supported by exuberant fibrous stroma, as well as scattered multinucleated floret-like giant cells. The tumor cells were immunopositive for vimentin, CD63, CD56, whereas AE1/AE3, S100, CD34, α-SMA, GFAP, EMA, CD57 and NSE were negative. Ki-67 was <2%. Multiple DCNs should be considered in the differential diagnosis of oral nodular lesions.
Keywords: Cellular neurothekeoma; Child; Desmoplastic cellular neurothekeoma; Immunohistochemistry; Oral cavity